2013
DOI: 10.1111/jasp.12046
|View full text |Cite
|
Sign up to set email alerts
|

Who opposes rights for persons with physical and intellectual disabilities?

Abstract: Research on human and civil rights has only rarely addressed people's attitudes toward disability rights in the context of American society. This study was designed to gain a better understanding of why certain individuals might oppose expanded rights for people who have disabilities. Pearson's correlations revealed that individuals high on social dominance orientation (SDO) and right-wing authoritarianism (RWA) were more likely to reject rights for persons with intellectual and physical disabilities than indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
(108 reference statements)
5
13
0
Order By: Relevance
“…We discuss our results below with this in mind. That both cognitive and affective prejudice about disabled sexuality predicted beliefs about the sexual rights of people with physical disabilities is consistent with prior research which has found that (affective) prejudice predicts opposition to the civil rights of disabled people [31].This is likely because denying that people with physical disabilities have sexual rights is functionally consistent with both cognitive prejudice (i.e. negative beliefs) and affective prejudice (i.e.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…We discuss our results below with this in mind. That both cognitive and affective prejudice about disabled sexuality predicted beliefs about the sexual rights of people with physical disabilities is consistent with prior research which has found that (affective) prejudice predicts opposition to the civil rights of disabled people [31].This is likely because denying that people with physical disabilities have sexual rights is functionally consistent with both cognitive prejudice (i.e. negative beliefs) and affective prejudice (i.e.…”
Section: Resultssupporting
confidence: 87%
“…In a similar vein, we find it plausible that affective discomfort about sexual/romantic relations with people with disabilities may also predict a lack of recognition of their sexual rights. This is consistent with Crowson et al [31] who found that affective prejudice predicts (explicit) opposition to human and civil rights for people with disabilities. We therefore suggest that, concurrently with cognitive prejudice, affective prejudice toward people with disabilities will predict lack of recognition of their sexual rights as an indirect expression of antipathy.…”
Section: Prejudicesupporting
confidence: 92%
See 3 more Smart Citations